Census of cultivable bacterial community in common effluent treatment plant (CETP) of tannery discharge and computational scrutiny on their leading residents - Suganya, Thangaiyan (Biomedical Informatics, 2013)
Common effluent treatment plant (CETP) for tannery effluent, is the combination of physical, chemical and biological treatment to facilitate the degradation of industrial waste water. Obviously, the biomass which survives in this extreme environment may have the ability to utilize the effluent as the sole carbon source for its survival. The ultimate aim of the present investigation is to expose the microbial diversity in each stage of the CETP through the culture dependent way. Bacterial diversity in the effluent were analysed through 16S rRNA gene. The community study revealed the dominance of firmicutes and the dominant genus was Bacillus sp, with variable species diversity. Notably, Putative Bacillus sp, B. firmus and B. licheniformis were observed in all stages of treatment. The dominant residents were analysed by BProm and TF site scan to prove their uniqueness. This species richness indicates the capability of liveliness in treatment plant and whose can be exploited for treating the effluent by using modern molecular approach. ABBREVIATIONS: CETP - Common Effluent Treatment Plant, PTIET - Pallavaram Tanners Industrial Effluent Treatment Company Ltd.